Arsenic: Association of regional concentrations in drinking water with suicide and natural causes of death in Italy. (March 2017) - Pompili, Maurizio; Vichi, Monica; Dinelli, Enrico; Erbuto, Denise; Pycha, Roger; Serafini, Gianluca; Giordano, Gloria; Valera, Paolo; Albanese, Stefano; Lima, Annamaria; De Vivo, Benedetto; Cicchella, Domenico; et al.
Abstract: Arsenic, as a toxin, may be associated with higher mortality rates, although its relationship to suicide is not clear. Given this uncertainty, we evaluated associations between local arsenic concentrations in tapwater and mortality in regions of Italy, to test the hypothesis that both natural-cause and suicide death rates would be higher with greater trace concentrations of arsenic. Arsenic concentrations in drinking-water samples from 145 sites were assayed by mass spectrometry, and correlated with local rates of mortality due to suicide and natural causes between 1980 and 2011, using weighted, least-squares univariate and multivariate regression modeling. Arsenic concentrations averaged 0.969 (CI: 0.543–1.396) µg/L, well below an accepted safe maximum of 10 µg/L. Arsenic levels were negatively associated with corresponding suicide rates, consistently among both men and women in all three study-decades, whereas mortality from natural causes increased with arsenic levels. Contrary to an hypothesized greater risk of suicide with higher concentrations of arsenic, we found a negative association, suggesting a possible protective effect, whereas mortality from natural causes was increased, in accord with known toxic effects of arsenic. The unexpected inverse association between arsenic and suicide requires further study. Highlights: We tested associations between local arsenic concentrations in tapwater and mortality in 145 regions of Italy. Surprisingly, arsenic levels were negatively associated with corresponding suicide rates, consistently among both men and women, and in all three study-decades. In contrast, as expected, mortality from natural causes increased with arsenic levels. The findings suggest that exposure to arsenic and perhaps other chemicals in drinking water may influence mental health to a degree that requires further study.